2020
DOI: 10.5812/ijp.99976
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Attention Deficit Hyper Activity Disorder After Early Exposure to General Anesthesia; A Case Control Study

Abstract: Background: Over the past decade, following the discovery that developing brain of immature animals was affected by anesthetic agents, the safety of general anesthesia (GA) in early life has been questioned. Objectives: We investigated the association between anesthesia exposure in children and ADHD development. Methods: This case-control study was conducted at pediatric psychology clinic of our institution and a pediatric neurology private clinic during 2019. Firstly the responsible resident of anesthesiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…I read the article entitled "Risk of attention deficit hyperactivity disorder after early exposure to general anesthesia; A case control study", by Sedighnejad et al (1), published in the third issue of the Iranian Journal of Pediatrics (2020) with great interest. The researchers concluded that early general anesthesia (GA) could be a predisposing factor for the subsequent development of attention deficit hyperactivity disorder (ADHD).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…I read the article entitled "Risk of attention deficit hyperactivity disorder after early exposure to general anesthesia; A case control study", by Sedighnejad et al (1), published in the third issue of the Iranian Journal of Pediatrics (2020) with great interest. The researchers concluded that early general anesthesia (GA) could be a predisposing factor for the subsequent development of attention deficit hyperactivity disorder (ADHD).…”
mentioning
confidence: 99%
“…The researchers concluded that early general anesthesia (GA) could be a predisposing factor for the subsequent development of attention deficit hyperactivity disorder (ADHD). They found that a history of GA in children younger than four years of age was a significant predictor of ADHD (1). After reading this article, as a pedodontist, I was concerned about the longterm anesthetic-induced neurodevelopmental outcomes of common dental procedures under GA.…”
mentioning
confidence: 99%
See 3 more Smart Citations